Separando a palha do bom grão: autoridade episcopal e disciplina eclesiástica em Cartago segundo o testemunho de Cipriano (século III d. C.) - Soares, Carolline da Silva (2016)
The episcopate of Cyprian in Carthage lasted only nine years, from 249 to 258. In that short time, however, the bishop produced a large number of works that tell us about the life and the problems faced by Christians in a time of instability in the Roman Empire and crisis within the Carthaginian church, since the period in which Cyprian wrote his works was marked by the first official persecution of Christians, first with Decius, in 249, and then, with Valerian, in 253. The corpus Cypriani allows us to observe how the contacts, conflicts and negotiations occurred in the Ancient city space, which enables an investigation of the set of capillar power relations between Christians and the disciplinary recommendations made by Cyprian in Carthage. Therefore, we analyze the conflict within the Carthage congregation concerning the re-baptism of the lapsi, that came up with the persecution of Decius and Valerian, and the socio-cultural and religious interactions that exists among Christians, pagans and Jews in the city of Carthage in mid-century III A.D., with the intention to elucidate the formation of religious boundaries between the adherents of Christianity, paganism and Judaism. In order to guide the Carthaginian congregation that he thought to have relaxed in the customs and practices, Cyprian recommended to Christians some disciplinary codes that should be adopted. Because of the yearning of standardize the Carthaginian congregation we highlight the importance of the works of Cyprian concerning the attempt to separate the Christians from the adherents of other faiths and of city spaces that the bishop assessed as dangerous, unclean and therefore able to polluting the assembly. We identify that the recommendations of Cyprian aimed at the formation of a “legitimate” Christian, free of hybridity and "impurities", i.e., a Christian who takes care of the sexual continence, of the alms and charity, of the prayer and discipline. For the Carthaginian bishop, the legitimate Christian should be a devotee who respects the episcopal authority, the legitimacy of the bishop and not attend the prohibited 14 areas of the city, own pagans and Jews. Given this situation, we defend the hypothesis that the period of “crisis” and persecution, characteristic of mid-third century, sparked a conflict in the Carthage church in which Cyprian tried to intervene as a regulator of behavior in order to define the legitimate Christian; and, that disciplinary determinations of Cyprian aimed at the organization and purity of the Carthaginian church in the third century against the behavior “inappropriate” of the the faithful who transited between Christian belief and habits and customs inherent to the pagan modus uiuendi and/or Jewish, own the classical city.